A Rapid Onset Refractory Perioperative Anaphylaxis: A Case of Fulminant Collapse Despite Aggressive Therapy - Yafi Rushan Rusli; Retti Kartika Bakti (Indonesian Journal of Anesthesiology and Reanimation, 2026)
Introduction: Perioperative refractory anaphylaxis is a rare but potentially catastrophic event that can rapidly progress to life-threatening cardiovascular and respiratory failure. Early recognition and prompt management are essential to prevent morbidity and mortality. Objective: This case report aims to report a rare case of rapid-onset refractory perioperative anaphylaxis with a fatal outcome despite prompt and aggressive resuscitative management. Case Report: A 35-year-old woman, classified as ASA Physical Status I, underwent an elective ovum pick-up procedure while receiving total intravenous anesthesia. She had no history of drug allergies and had previously tolerated general anesthesia without complications. Standard monitoring was applied, and intravenous cefazolin was administered preoperatively according to institutional protocol. Anesthesia was induced with fentanyl, propofol, and ketamine, followed by ketorolac and ondansetron. Approximately 20 minutes after induction, while the cefazolin infusion was ongoing, the patient developed a progressive decline in oxygen saturation despite a patent airway and effective assisted ventilation, followed by diffuse violaceous flushing of the trunk and extremities, raising strong suspicion of severe anaphylaxis. Immediate resuscitative measures were initiated, including Code Blue activation, escalating intravenous adrenaline boluses, and endotracheal intubation with confirmed bilateral breath sounds and no evidence of bronchospasm. Despite high-flow oxygen, aggressive fluid resuscitation, and corticosteroid administration, oxygen saturation continued to deteriorate and became unobtainable. Hemodynamics later progressed to cardiac arrest with documented asystole. Prolonged advanced cardiopulmonary resuscitation was performed without returning spontaneous circulation. During resuscitation, fresh blood was noted from the endotracheal tube, suggesting catastrophic capillary leak and disseminated intravascular coagulation. Resuscitative efforts were terminated, and the patient was pronounced deceased. Conclusion: Perioperative anaphylaxis may progress rapidly to fatal refractory shock, even in healthy patients. High clinical suspicion, early recognition, and institutional preparedness are essential despite prompt and aggressive management.